Experimental Investigation of Lateral Stresses and Bearing Capacity of Sandy Soil Under Shallow Foundation Loads - Aksoy, Huseyin Suha; Kayaalp, Damla Kucukay (Mdpi, 2025)
While existing analytical methods provide solutions for calculating vertical pressures in soil, calculating lateral stresses remains a critical challenge. Therefore, experimentally measuring stress values is essential, considering the various factors influencing these stresses. This study investigates the lateral stress variations occurring beneath foundations placed on sandy soil and assesses the ultimate bearing capacity and settlement behavior of these foundations. Additional lateral stresses were measured beneath square shallow foundations on the sand with varying relative densities. The model tests were conducted in a square-sectioned sand tank. The results revealed that the lateral stress values tended to increase with both the foundation size and soil density, with this effect being most pronounced at a relative density of 90%. Furthermore, the lateral stresses decreased with increasing depth beneath the foundation for all foundation sizes. Loading tests were performed on square foundations of various sizes placed on sand prepared at different relative densities. A significant increase in the ultimate bearing capacity was noted as the foundation size and relative density of the soil increased. The measured lateral stresses were compared with theoretical predictions, and it was found that the values derived from the theoretical equations aligned well with the experimental results. In the second part of the study, a regression analysis was conducted to predict the lateral stresses within the soil. It was concluded that lateral stresses can be estimated with a high degree of accuracy using the proposed regression model (R2 = 0.982).
Keywords: shallow foundation; bearing capacity; lateral stress; relative density; model experiment; sand